[Review] Investigating the Challenges of Promoting Dark Tourism in Rwanda - Korstanje, Maximiliano E (Revista Rosa dos Ventos - Turismo e Hospitalidade, 2019)
ABSTRACT J. Ntunda interrogates to what extent dark tourism would be a product to be fostered in Rwanda. Based on formal interviews done over 43 specialists who take part of RDB [Rwanda Development Board], Ntunda holds that several incompatibilities which include lack of skilled staff and problems in the accessibilities to the site prevent today dark tourism would be a valid option. However, we live in a hyper-globalized world where information is produced, packaged and disseminated in minutes to a broader audience. In this new world, there is no place to hide. Therefore, specialists and policymakers should promote Rwanda taking advantage of global sources and the information which is digitally designed. REVIEWED BY Maximiliano E Korstanje – Doutorando em Psicology Social, Universidad John Kennedy, Buenos Aires, Argentina. Professor University of Palermo, Buenos Aires, Argentina. Currículo: http://ciberconta.unizar.es/cv/maxikorstanje.htm. E-mail: maxikorstanje@hotmail.com REFERENCES Korstanje M. (2016) The rise of thana capitalism and tourism. Abingdon, Routledge. Ntunda, J, (2014). Investigating the challenges of promoting Dark Tourism in Rwanda. Hamburg: Anchor Academic Publishing. Stone, P. R. (2012). Dark tourism and significant other death: Towards a model of mortality mediation. Annals of Tourism Research, 39(3), 1565-1587. Link Tzanelli, R. (2016). Thanatourism and cinematic representations of risk: screening the end of tourism (V. 176). Abingdon: Routledge.